2021
DOI: 10.1111/ejn.15559
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility and added value of mapping music during awake craniotomy: A systematic review

Abstract: The value of mapping musical function during awake craniotomy is unclear.Hence, this systematic review was conducted to examine the feasibility and added value of music mapping in patients undergoing awake craniotomy. An extensive search, on 26 March 2021, in four electronic databases (Medline, Embase, Web of Science and Cochrane CENTRAL register of trials), using synonyms of the words "Awake Craniotomy" and "Music Performance," was conducted. Patients performing music while undergoing awake craniotomy were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In professional musicians, only very few cases of awake surgery have been reported. [16][17][18][19]57,58 In these series, the musical performance or music production was mapped during DES. However, beyond the fact that it may be difficult to play some instruments in a surgical setting (e.g., due to the risk of brain swelling by playing wind instruments such as the saxophone), as well as the difficulty in combining music performance with other tasks (it seems unlikely that one could play drums or the oboe while naming objects), using only a music task as if musical skills were a discrete cognitive function seems reductionist and based on a modular view of brain functioning, as if music ability was subserved by an isolated, specific circuit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In professional musicians, only very few cases of awake surgery have been reported. [16][17][18][19]57,58 In these series, the musical performance or music production was mapped during DES. However, beyond the fact that it may be difficult to play some instruments in a surgical setting (e.g., due to the risk of brain swelling by playing wind instruments such as the saxophone), as well as the difficulty in combining music performance with other tasks (it seems unlikely that one could play drums or the oboe while naming objects), using only a music task as if musical skills were a discrete cognitive function seems reductionist and based on a modular view of brain functioning, as if music ability was subserved by an isolated, specific circuit.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,6 Beyond being a perfectly designed vehicle to evoke emotions, the ability to create music necessitates, in addition to sensorimotor and auditory skills, an optimum interaction between several higherorder functions mediating perception, 5,7,8 attention, 9 selfawareness 10,11 and metacognition, 12 creativity, 13 emotional processing, 5,6 and social cognition. 14,15 Despite this large framework involved in musical skills, previous case series in the literature reported the results of awake surgeries for brain tumors in musicians focusing mainly on music performance by means of singing, humming, melody recognition, score reading, or instrument performance, [16][17][18][19] as if this complex ability could be reduced to a modular function that would be subserved by a specific network acting in isolation. In fact, because music ability is subserved by a mosaic of interactive cognitive and emotional processes that rest on several networks, our main goal was to carry out an intraoperative complex cognitive assessment individualized to each patient from a meta-networking standpoint, 20,21 namely, by taking into consideration coordination between sensorimotor function and language as well as higher-order functions such as semantics and mentalizing.…”
mentioning
confidence: 99%
“…To date, 20 patients have been reported in the literature of AC for brain tumor resection to map different forms of musical function, not including ours. Furthermore, there is only 1 review of the literature, which encased craniotomies for all causes [ 8 ]. In this review, we specifically focus on brain tumor resections to analyze the benefits of this approach in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…It may be reasonable to include musical mapping during AC for brain tumor resection in patients who require their musical skills for personal or professional reasons. Recently, Kappen et al [ 8 ] performed a systematic review of patients performing music during AC which showed that mapping music is feasible. In this case report, we explore our experience with AC for brain tumor resection in a patient that played an instrument (guitar) and sang simultaneously during surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Music services like last.fm are available, as are reviews, biographies, journals, and music-related RSS links on the World Wide Web. Literature [2] uses joint filtering to implement music recommendations. It has an excellent statistical effect on popular songs.…”
Section: Introductionmentioning
confidence: 99%